Effect of Antiprogestrogen on Myometrial Thickness and Progesterone/Estrogen Receptors in the Rat Myometrium - Khadija Qamar ,Liaqat Ali Minhas , Zarmina Saga (Journal of Rawalpindi Medical College, 2012)
Background: To study the histomorphological effects of Mifepristone treatment on rat uterus. Methods: In this experimental study, sixty adult female rats were divided randomly into two groups, comprising of 30 animals in each group. In group A one ml of normal saline was given orally daily for three months while in group B mifepristone was given orally in a dose of 1 mg/kg body weight daily for three months. All the animals were sacrificed next day after the last oral dose. Two ml blood was taken directly from the heart for measurement of estrogen and progesterone levels. About ½ cm piece of tissue was taken from the middle of the right uterine horn. Sections were cut and immunohistochemical staining procedure was done for demonstration of progesterone and estrogen receptors Results: In the experimental group the number of progesterone and estrogen receptors in the uterine myometrium of the experimental group were decreased and found statistically significant. Significantly lower level of progesterone while higher levels of estrogen level were noted in the experimental group as compared to control group. In the experimental group thickness of the myometrium was reduced Conclusion: Long term mifepristone (Antiprogesterogen) administration suppresses the endometrial proliferation. It decreases the number of progesterone and estrogen receptors. It lowers the serum levels of progesterone, while estrogen levels elevates it.